Promoting interdisciplinary approaches to solving the complexity of environmental problems in Indonesia - Monk, Kathryn A. (Indonesian Journal of Applied Environmental Studies, 2020)
As an ecologist, I believe we are now seeing the maturing of what we could call the Age of Ecology. An Age in which we finally develop that coherent and essential mainstream narrative for our future; one in which we tackle the interdependencies of nature loss, the climate emergency, and unsustainable production and consumption.The challenge has always been to recognise that the world is our bank account, and we live sustainably only by using its interest, not digging into our capital. If we do withdraw more capital, we must then find ways of investing more, to increase our capital. You can hear this language finally gaining much more traction today as politicians, managers and the public use the phrases natural and social capital, as well as the financial and manufactured capital, and recognise our dependencies on the natural environment.As such, I fully support the holistic, interdisciplinary sentiments and recommendations of Purwanto et al. (2020) in their introduction to the first issue of the Indonesian Journal of Applied Environmental Studies (InJAST).  I have promoted interdisciplinary approaches to solving complex environmental problems throughout my career and worked with other academics and practitioners to support the realisation of the societal and economic impact of their research. We have increasingly recognised research impact institutionally and financially, but one main weakness persists and that is the availability of academic journals for publishing such interdisciplinary work. This journal can offer such a space for researchers and encourage the recognition and promotion of evidence to policy and practice communications.  Most of all, this journal can foster the culture and confidence to ask the right questions to support the development of evidence-based decision making in policy and operational activities.  I have spent a lot of time working with researchers who are doing excellent research but not asking the best questions to help improve management and utilisation of natural resources.  Providing a forum in which students and early career researchers can confidently explore the rough answers to the right questions rather than the precise answers to the wrong questions, to paraphrase John Tukey (19152000), would be a wonderful role for InJAST.I am delighted to be asked to share my environmental experiences and perspectives in this guest editorial for the second issue of InJAST, reflecting for me a long association with Indonesia and Indonesian environmental managers, conservationists and foresters. I have worked around the world, especially in the tropics, firstly as part of scientific expeditions and then leading increasingly complex research and development programmes and institutions. Since returning to the UK, I have been involved in enhancing the quality and impact of scientific and interdisciplinary research and supporting the application and institutionalisation of the ecosystem approach and ecosystem services assessments. Here, I will focus on three major tropical environmental management programmes, two in Indonesia and one in Guyana, South America.These were complemented by subsequent involvement in the UK Governments environmental management system. All reflect the evolution of environmental management and the emergence of the ecosystem approach, now being institutionalised slowly but surely around the world.